Congestion Control in Communication Networks with Variable Discretization Period - Molik, Tomasz; Bartoszewicz, Andrzej; Ignaciuk , Przemysław (Journal of Applied Computer Science, 2006)
In this paper, discrete flow control mechanism for connection-oriented telecommunication networks is proposed. In the considered system the feedback information about the current network state is delivered to the sources for the purpose of rate adaptation in discrete moments of time, however, the sampling period does not remain constant, but may change during the execution of the control process. The applied nonlinear algorithm allows eliminating data losses and ensures full usage of the available bandwidth. Since the rates generated by the controller are always nonnegative and bounded, the described strategy can be directly applied in real telecommunication systems.